The Short‐ and Mid‐term Follow‐Up of Single‐Column Fixation in Transverse and Posterior Wall Acetabular Fractures. Issue 1 (5th December 2021) - Yang, Yun; Sun, Jiachen; Xiang, Zhou
Abstract : Objective: To evaluate the radiological and clinical outcomes of the surgical treatment for transverse and posterior wall fractures using single‐column posterior fixation. Methods: From January 2009 to January 2018, a total of 24 patients with transverse and posterior wall acetabular fractures in our center were included in this retrospective study, including 17 males and seven females with a mean age of 47 years and a minimum follow‐up of 1 year. All cases were closed fractures. All fractures were fixed with single‐column fixation via the Kocher–Langenbeck approach. Primary outcome measures, including quality of reduction and clinical outcomes, were recorded by an independent observer, who also noted secondary outcome measures, including time to surgery, surgical time, intraoperative blood loss, and postoperative complications. Results: Twenty‐four patients (range, 26–74 years) included 17 males and seven females. There were 14 cases on the left side and 10 cases on the right side. The mean time from injury to surgery was 7.1 days. Mean intraoperative blood loss and surgical time were 405.4 mL and 135.8 min, respectively. The mean follow‐up time was 29.5 months (range 12–96 months). All the acetabular fractures united within 5 months after surgery. The quality of reduction was graded as anatomical in 17 cases (70.8%), imperfect in three cases (12.5%), and poor in four cases (16.7%). According to grading system of Merle d' Aubigne and Postel, clinical outcomes at the final follow‐up were excellent in 10 cases (41.7%), good in six cases (25.0%), fair in five cases (20.5%), and poor in three cases (12.5%). The excellent and good rate was 66.7%. There was a significant relation between the quality of reduction and clinical outcomes ( P < 0.05). At follow‐up, there were one case of sciatic nerve injury, one case of wound infection, two cases of deep vein thrombosis, two cases of avascular necrosis, three cases of heterotopic ossification, and five cases of postoperative traumatic arthritis. Three of these patients underwent reoperation, including one with heterotopic ossification affecting hip movement and two with femoral head necrosis. Conclusions: Our study shows that single‐column posterior fixation of transverse and posterior wall acetabular fracture through the Kocher–Langenbeck approach can obtain satisfactory radiological and clinical outcomes if there is adequate indirect reduction of the anterior column. Abstract : Posterior column fixation alone in transverse and posterior wall fractures can obtain satisfactory radiological and clinical outcomes. Direct reduction and fixation of the posterior wall and column components by the Kocher–Langenbeck approach is an adequate option for these injuries.